OBTAINING STRAIN-PRODUCER OF RECOMBINANT HEXON OF BOVINE ADENOVIRUS TYPE 3 - Mukantayev , K.N.; Tursunov , K.A.; Kanayev, D.B.; Tokhtarova, L.; Ramankulov, Ye. M.; Mukanov , K. K. (Eurasian Journal of Applied Biotechnology, 2019)
The diagnosis of bovine adenovirus is difficult due to a large number and identity of clinical symptoms with various diseases. For the diagnosis of adenoviral infection using various methods such as the isolation of the virus, in situ hybridization, enzyme-linked immunosorbent assay (ELISA), immunofluorescence, restriction analysis and polymerase chain reaction (PCR). The methods used are time consuming and require expensive equipment. In this regard, obtaining recombinant virus antigens of diagnostic importance is very important. One of the important diagnostic antigens is hexon, a group-specific protein that induces the formation of group-specific antibodies. Under de novo conditions, the gene of the N-terminal fragment of hexon of BAV-3 with a length 503 base pairs was synthesized. A strain of E. coli BL21/pET28/rhAdv3 producing recombinant hexon of BAV-3 (rhAdv3) was obtained. The protein produced by the strain BL21/pET28/rhAdv3 contains a hexa-histidine tag and has a molecular weight of 25 kDa. An analysis of the MS/MS data using the Mascot program and the SwissProt database showed that the highest rate (Score 2033) corresponded to a fragment of hexon of BAV-3. The gene of the fragment of the N-terminal part of the hexon of BAV-3 was synthesized. The genetic construct pET28/rhAdv3 and the microorganism strain BL21/pET28/rhAdv3 producing rhAdv3 protein were obtained. rhAdv3 has the potential to develop test systems designed to diagnose adenoviral infection of farm animals.